Pengaruh model pembelajaran Missouri Mathematics Project (MMP) terhadap kemampuan representasi matematis siswa ditinjau dari Adversity Quotient (AQ) - Neneng Maulida; Muin, Abdul; Kustiawati, Dedek (IKIP Siliwangi, 2025)
The research's background is students' poor representation skills. This investigation sought to determine how the Adversity Quotient (AQ) and Missouri Mathematics Project (MMP) learning models affected students' capacity for representation of mathematics. During the even semester of the 2023–2024 school year, this research was conducted at one of the MTs in South Tangerang City. Using the cluster random sampling method, 45 learners were chosen for the study, 23 of them were from the experimental class and 22 from the control class. Each class is divided into three levels of AQ which are students with Quitters, Camper, and Climber types. This study used a design similar to an experiment with a control group that was only included in the post-test. The data analysis technique used is two-way ANOVA testing. The findings of the investigation indicate that 1) students' mathematical modeling skills are influenced by their acquisition of model; 2) students' mathematical representation skills are influenced by the AQ type; and 3) there is no interaction effect between the AQ type and learning model on pupils mathematically illustration skills.